Self, value, and narrative a Kierkegaardian approach - Rudd, Anthony, 1963- (Oxford : Oxford University Press, 2013)
Anthony Rudd presents a new account of the self as an ethical evaluative being. He draws on Kierkegaard's thought to present a case for an ancient and currently neglected view: that the tensions which are constitutive of selfhood can only be reconciled through the understanding of the self as guided by an objective Good.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: d; Self (Philosophy)